Concordance between 8-1-1 HealthLink BC Emergency iDoctor-in-assistance (HEiDi) virtual physician advice and subsequent health service utilization for callers to a nurse-managed provincial health information telephone service - Ross Duncan; Kurtis Stewart; Frank X. Scheuermeyer; Riyad B. Abu-Laban; Kendall Ho; Danielle Lavallee; Jim Christenson; Nancy Wood; Stirling Bryan; Lindsay Hedden (BMC, 2023)
Abstract Background British Columbia 8-1-1 callers who are advised by a nurse to seek urgent medical care can be referred to virtual physicians (VPs) for supplemental assessment and advice. Prior research indicates callers' subsequent health service use may diverge from VP advice. We sought to 1) estimate concordance between VP advice and subsequent health service use, and 2) identify factors associated with concordance to understand potential drivers of discordant cases. Methods We linked relevant provincial administrative databases to obtain inpatient, outpatient, and emergency service use by callers. We developed operational definitions of concordance collaboratively with researcher, patient, VP, and management perspectives. We used Kaplan-Meier curves to describe health service use post-VP consultation and Cox regression to estimate the association of caller factors (rurality, demography, attachment to primary care) and call factors (reason, triage level, time of day) with concordance as hazard ratios. Results We analyzed 17,188 calls from November 16, 2020 to April 30, 2021. Callers advised to attend an emergency department (ED) immediately were the most concordant (73%) while concordance was lowest for those advised to seek Family Physician (FP) care either immediately (41%) or within 7 days (47%). Callers unattached to FPs were less likely to schedule an FP visit (hazard ratio = 0.76 [95%CI: 0.68-0.85]). Rural callers were less likely to attend an ED within 48 h when advised to go immediately (0.53 [95%CI:0.46-0.61]) compared to urban callers. Rural callers advised to see an FP, either immediately (1.28 [95%CI:1.01-1.62]) or within 7 days (1.23 [95%CI: 1.11-1.37]), were more likely to do so than urban callers. Interpretation Concordance between VP advice and subsequent caller health service use varies substantially by category of advice and caller rurality. Concordance with advice to "Go to ED" is high overall but to access primary care is below 50%, suggesting potential issues with timely access to FP care. Future research from a patient/caller centered perspective may reveal additional barriers and facilitators to concordance.